Malaysian PBL Approaches: Shaping World-Class TVET Skills towards IR 4.0 - Rohanai, Reyanhealme; Othman, Hasyamuddin; Azhar Mat Daud, Khairul; Huda Omar, Nurul; Ahmad, Maimunah; Erfy Ismail, Mohd; Sulaiman, Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
An Industrial Revolution 4.0 promoted by the Malaysian government entitles the rapid growth of the manufacturing sector, thus promoting a multi-level of workforce and skilled work force needed to satisfy the rapid technological development application. The challenges arise in preparing the individuals to meet with the current business at an adequate skill level, and the student needs to be prepared in such a way that they satisfy the business expectations. Looking into this situation, this paper aims to study the concept of correlation between the active learning method known as the problem-based learning (PBL) method and the required employability skills in TVET. As an initiative to enrich the future opportunity of empowering TVET skills, this study assumes that there is a positive relationship between employability skills and PBL approaches in improving student’s quality and skills. The method of study involves documentation analysis on previous research to prove the importance of employability skills in enhancing student’s competencies and the effectiveness of the problem-based learning method in preparing the students to meet the expectations. The main findings of this study claimed that there was a positive relationship between employability skills and PBL learning methods. The results acknowledge that PBL has the ingredients to help develop employability skills and student’s behavior. Through PBL, students learn to become more associates in the teaching and learning processes as they take responsibility throughout the learning process. It would suggest that the educational institution should emphasize the needs of the industry and students by creating awareness and guiding the students in self-analysis and in the acquisition of skills.